Memaknai Diskriminasi: Pengalaman Hidup Perempuan Tunanetra dalam Perspektif Fenomenologi - Iqbal, Muhammad; Ayyub Damran; Dwia Aries Tina Pulubuhu; Nuvida RAF (Nirta Learning Centre, 2025)
AbstractDiscrimination against blind women represents a complex phenomenon that intertwines gender inequality with disability stigma. This study aims to examine how they understand and respond to discriminatory experiences in their everyday lives using a qualitative phenomenological approach. Data were collected from eight members of the Indonesian Women with Disabilities Association (HWDI) in Polewali Mandar through interviews, participant observation, and document analysis. The findings reveal that discrimination occurs across family, social, and economic domains, and is experienced as being invisible, being devalued, and losing control over personal life. Nevertheless, the informants negotiate these experiences through self-reflection, religious beliefs, and support from HWDI as a space for identity recovery. This study concludes that discrimination is not merely a factual event but a social process that shapes self-concept and survival strategies, emphasizing blind women’s role as active subjects while contributing to the literature on disability sociology and inclusive policy development.